Successful resuscitation of acute type A aortic dissection with pulmonary embolism using long-term venoarterial extracorporeal membrane oxygenation: a case report - Zhu, Guiwei; Yue, Wenhui; Li, Yanmin; Wang, Haiqing; Li, Jianqiang; Zhou, Xin; Zhang, Qinghai; Zhang, Jihong (Frontiers in Medicine, 2025)
Acute aortic dissection (AAD) and pulmonary embolism (PE) are two critical and potentially fatal causes of chest pain. The simultaneous occurrence of these conditions is exceptionally rare; however, when they co-occur, the conflicting therapeutic strategies required significantly elevate mortality rates. While venoarterial extracorporeal membrane oxygenation (VA-ECMO) has been extensively reported as a life-saving intervention for high-risk pulmonary embolism, its application in the management of AAD remains highly debated. Recently, our institution successfully employed VA-ECMO to treat a patient with acute type A aortic dissection (ATAAD) complicated by PE. This case highlights that VA-ECMO may serve as a crucial life-saving measure for patients with AAD who present with hemodynamic instability or cardiac arrest.